Preliminary Survey and Study of the CymMV Variability in Orchids of Sao Paulo State, Brazil - Moraes, L. A. [UNESP]; Pavan, M. A. [UNESP]; Sakate, R. K. [UNESP]; Blystad, D. R.; Spetz, C.; Floistad, E. (Int Soc Horticultural Science, 2015)
Viruses are a major problem in orchid production systems, as they promote considerable damage to its commercial value, since they directly affect its aesthetic appeal as well as productivity. The Potexvirus Cymbidium mosaic virus (CymMV) and the Tobamovirus Odontoglossum ringspot virus (ORSV) are of great economic importance worldwide. A survey of the viruses present in 232 orchid samples belonging to different genera and collected from 12 Sao Paulo State cities was carried out. The diagnosis was made by direct ELISA test for the detection of CymMV, ORSV, TSWV (Tomato spotted wilt virus), and CymRSV (Cymbidium ringspot virus), as well as indirect ELISA for Potyvirus detection, using universal antiserum against this genus. The results were confirmed by RT-PCR, with specific oligonucleotides designed for the coat protein (CP) gene of the CymMV and ORSV, as well as for the detection of Orchid fleck virus (OFV). Of the total of samples tested, 153 were positive for CymMV (65.9%), and 40 were positive for ORSV (17.2%). CymRSV, TSWV, OFV or any Potyvirus were not found in the samples analyzed. In 90% of the samples in which ORSV was detected, CymMV was also present in mixed infections. Nucleotide identity of the CymMV sequenced isolates ranged between 91 and 92% with CymMV genbank accession numbers AY571289.1, AB541572.1 and AB197937.1, and the phylogenetic tree supposes that, so far, this virus has shown a low variability rate, in terms of CP gene. These results denote the CymMV importance in the orchid production systems in Sao Paulo State, as well as possible synergistic link between this virus and ORSV.
Keywords: detection; symptoms; Orchidaceae; Cymbidium mosaic virus; Odontoglossum ringspot virus